PENGARUH MEDIA SMART BOOK TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA - Mulyani, Ai Hani; Suryaningrat, Eko Fajar; Pujiasti, Dea Asri; Mutaqin, Ejen Jenal (IPI Press, 2022)
This study aims to determine the effect of smart book media on elementary school’s mathematics problem solving abilities, with the subject of plane shapes which focusing on the cognitive abilities. This study method uses is an experimental (pre-experimental) from a quantitative approach with a design one group pretest-posttest design. The sampling technique in this research is non-probability sampling, which is saturated sampling with a sample used 21 students. The research was carried out at SDN Sindanghurip located in Salawu. The instrument used is a written test in the form of an essay questions test.. Furthermore, the results of the t-test calculation obtained t_count = 11.51 and t_table = 2.08596, because the value of t_count = 11.51 outside the acceptance area of ​​​​ H₀, so H₀ is rejected and H₁ is accepted. Therefore, it can be concluded that the use of smart book media of can affect the mathematical problem solving abilities of elementary on subject of plane shapes that focus on student’s cognitive abilities, precisely on fifth grade students at SDN Sindanghurip.